You are on page 1of 6

A new renewal type of sequence

Edward Omey
HUB - Stormstraat 2
1000 Brussels - Belgium
edward.omey@hubrussel.be
1 Introduction
Let X; X(1); X(2); ::: denote independent random variables with the same dis-
tribution given by P(X = 1) = p and P(X = 2) = q = 1 p where 0 < p < 1.
For x 1 we consider the following counting process:
N(x) = minfn :
n
i=1
X(i) > xg ,
and let H(x) = E(N(x)). In this paper, among others we determine H(x)
together with some of its properties. For x < 1, we trivially have N(x) = 1.
2 The process N(x)
It is clear that the products X(1)X(2):::X(n) can take values only in the set
f1; 2; 4; 8; :::g =
¸
2
k
; k 0

. This implies that for 1 x < 2 we have N(x) =
N(1) and that for 2
m
x < 2
m+1
we have N(x) = N(2
m
).
Now consider x = 1 and N(1). It is clear that the product crosses the value 1
for the …rst time if we have a sequence of outcomes 1 followed by a last outcome
2. It follows that
P(N(1) = k) = qp
k1
, k 1.
Next consider x = 2
m
and N(2
m
). It is clear that the product crosses the
value 2
m
for the …rst time at experiment k if we have k 1 experiments with
exactly m1 times the outcome 2 and the remaining outcomes equal to 1. The
k-th outcome has to be 2. It follows that
P(N(2
m
) = k) =

k 1
m1

q
m
p
km
, k m.
Clearly N(2
m
) has a negative binomial distribution NEGBIN(m+ 1; q).
Using elementary properties of the negative binomial distribution, we obtain
the following result. Let H(x) = E(N(x)) and V (x) = V ar(N(x)).
Proposition 1 For k 0, we have
H(2
m
) =
m+ 1
q
,
V (2
m
) =
(m+ 1)p
q
2
.
1
In terms of x, we can …nd the …rst value of m such that 2
m
x < 2
m+1
and
we …nd that
H(x) =
1
q
(
¸
log(x)
log(2)
¸
+ 1), (1)
V (x) =
p
q
H(x).
From the properties of the negative binomial distribution, we also have the
following central limit theorem for N(x).
Proposition 2 As x !1, we have
N(x) log(x)=(q log(2))

p log(x)=q
2
d
=)Z,
where
d
=) denotes convergence in distribution and Z has a standard normal
distribution.
3 Some properties of the function H(x)
Using formula (1), it is easy to see that
H(2x) =
1
q
(
¸
log(2x)
log(2)
¸
+ 1) =
1
q
+H(x).
From (1) it also follows that as x !1,
H(x) s
log(x)
q log(2)
. (2)
If we consider the di¤erence D(x) given by
D(x) = H(x)
log(x)
q log(2)
,
we get that 0 D(x) 1=q.
Remark 1. That we have result (2) is not a surprise. In renewal theory on
considers counting processes of the form
N(x) = minfn : Y (1) +Y (2) +::: +Y (n) > xg ,
where the Y (i) are i.i.d. nonnegative random variables. The renewal function
is de…ned as H(x) = E(N(x)).
In renewal theory, the elementary renewal theorem states that as x !1,
1
x
H(x) !
1

,
2
where = E(Y ). In our problem we have
N(x) = minfn :
n
i=1
X(i) > xg
= min

n :
n
¸
i=1
log(X(i)) > log(x)
¸
.
Clearly we have E(log(X)) = q log(2).
Remark 2. If we consider the di¤erence
D

(x) = H(x)
1
q
¸
log(x)
log(2)
¸
,
we trivially have that D

(x) = 1=q.
4 Generating functions
4.1 The Mellin transform
The Mellin transform of a measurable function f : (0; 1) ! (1; +1) is
de…ned as
´
f(z) =

1
0
f(x)x
z1
dx,
for z such that the integral converges.
For z > 0, we have
´
H(z) =

1
1
H(x)x
z1
dx
=
1
¸
m=0

[2
m
;2
m+1
)
H(x)x
z1
dx
=
1
¸
m=0
m+ 1
q

[2
m
;2
m+1
)
x
z1
dx
=
1
¸
m=0
m+ 1
q
1
z
(2
(m+1)(z)
2
m(z)
)
=
1 2
z
qz
1
¸
m=0
(m+ 1)2
zm
=
1 2
z
qz
1
(1 2
z
)
2
=
1
qz(1 2
z
)
We conclude that
´
H(z) =
1
qz(1 2
z
)
, z > 0.
3
Note that for z !0, we have 1 2
z
= 1 e
z log(2)
s z log(2), so that
´
H(z) s
1
q log(2)
1
z
2
.
Note that for z > 0, we have

1
1
log(x)x
z1
dx =
1
z

1
1
x
z1
dx =
1
z
2
.
This con…rms the asymptotic formula
H(x) s
log(x)
q log(2)
.
Remark 3. We look at the di¤erence
D(x) = H(x)
log(x)
q log(2)
.
For the Mellin transform we …nd
´
D(z) =
1
qz(1 2
z
)

1
z
2
1
q log(2)
=
1
qz log(2)

z log(2) 1 + 2
z
(1 2
z
)

s
1
qz log(2)
z
2
(log(2))
2
2 log(2)z
=
1
qz
.
Also, we have

1
1
1
q
x
z1
dx =
1
qz
.
This example shows that the Tauberian implication
´
D(z) s 1=(qz) implies that
D(x) s 1=q is false.
4.2 A generating function
If we consider the sequence a(n) = n, n 0, we get that
¯a(z) =
1
¸
n=0
z
a(n)
=
1
1 z
.
For the sequence H(n) and for suitable values of z, we …nd that
¯
H(z) =
1
¸
k=1
z
H(k)
=
1
¸
m=0
2
m+1
1
¸
k=2
m
z
H(k)
=
1
¸
m=0
z
(m+1)=q
(2
m+1
2
m
)
= z
1=q
1
1 (2z)
1=q
.
4
4.3 The generating function
It seems to be di¢cult to …nd a nice expression for the usual generating function
H(z) =
¸
1
n=1
H(n)z
n
. To obtain an expression, we consider the following
sequence:
H(1)
H(2) H(1)
:::
H(n) H(n 1)
:::
Clearly we have H(1) = 1=q. For n 2 we have H(n) H(n 1) = 1=q for
all n of the form n = 2
k
and we have H(n) H(n1) = 0 in all other cases. It
follows that
H(1)z +
1
¸
n=2
(H(n) H(n 1)z
n
=
1
q
1
¸
m=0
z
2
m
.
Rearranging the terms, we …nd that
H(z) =
1
q(1 z)
1
¸
m=0
z
2
m
.
Clearly H(z) satis…es the following relation:
H(z) =
z
q(1 z)
+ (1 +z)H(z
2
).
Using F(z) = (1 z)H(z), we get that F(z) = z=q +F(z
2
).
5 Example
Let us take p = q = 1=2. In this case we obtain that for m = 0; 1; 2; ::: and
2
m
x < 2
m+1
, we have
H(x) = H(2
m
) = 2(m+ 1):
The sequence H(n) looks as follows:
2; 4; 4; 6; 6; 6; 6; 8; 8; 8; 8; 8; 8; 8; 8; 10; 10; :::10; :::
1 times 2
2 times 4
4 times 6
8 times 8
16 times 10
2
m
times 2(m+ 1).
5
6 Extensions
It is clear that we can do a similar analysis starting from a random variable
with pdf
P(X = 1) = p, P(X = c) = q = 1 p,
where 0 < p < 1, and c 2 is an integer. For any x 1, we can …nd the value
of m such that c
m
x < c
m+1
and we have that
H(x) =
1
q
(
¸
log(x)
log(c)
¸
+ 1),
H(c
m
) =
m+ 1
q
.
7 Bibliography
1. W. Feller, An Introduction to Probability Theory and Its Applications.
Vol. I, Vol II, Wiley, New York, 1966.
2. S.M. Ross, Applied Probability Models with Optimization Applications.
Holden-Day, San Francisco, 1970.
3. Weisstein, Eric W. "Mellin Transform." From MathWorld–A Wolfram
Web Resource. http://mathworld.wolfram.com/MellinTransform.html
6